2020
DOI: 10.1371/journal.pone.0229517
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir-based regimens in the treatment of patients with chronic hepatitis C virus infection: Real-world efficacy in Thailand

Abstract: AimsTo analyze the efficacy and safety of sofosbuvir (SOF)-based regimens in Thai patients with chronic hepatitis C virus infection who had pre-existing significant liver fibrosis. Patients and methodsThis was a retrospective cohort study, conducted between 1 June 2018 and 31 May 2019 at Rajavithi Hospital, Bangkok, Thailand. All patients completed 12 weeks of SOF-based regimens and had follow-up for at least 12 weeks after therapy discontinuation. The primary outcome was sustained virological response (SVR) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
5
5
0
Order By: Relevance
“…Tran et al suggested that obesity, defined as BMI ≥ 30 kg/m2, did not have negative impact on virological response of CHC patients treated with DAA agents 29 . This observation was further confirmed by several other authors 30,31 . However, in a large study of 6961 patients treated with 8 or 12 weeks of LDV/SOF ± RBV or 12 weeks of OPrD ± RBV, high BMI was found to be a significant negative predictor of SVR 32 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Tran et al suggested that obesity, defined as BMI ≥ 30 kg/m2, did not have negative impact on virological response of CHC patients treated with DAA agents 29 . This observation was further confirmed by several other authors 30,31 . However, in a large study of 6961 patients treated with 8 or 12 weeks of LDV/SOF ± RBV or 12 weeks of OPrD ± RBV, high BMI was found to be a significant negative predictor of SVR 32 .…”
Section: Discussionsupporting
confidence: 53%
“…29 This observation was further confirmed by several other authors. 30,31 However, in a large study of 6961 patients treated with 8 or 12 weeks of LDV/ SOF ± RBV or 12 weeks of OPrD ± RBV, high BMI was found to be a significant negative predictor of SVR. 32 Considerably lower SVR rates for patients with significant steatosis based on biopsy samples compared to controls have also been reported after interferon (IFN)/ ribavirin or pegylated IFN/ribavirin therapies.…”
Section: Discussionmentioning
confidence: 98%
“…The overall SVR rate (96.9%) was comparable to previously reported findings. 15 , 16 , 17 , 18 The rate of SVR in real‐world setting was not different between the HCV mono‐infection group and the HIV/HCV co‐infection group (96.9% vs 96.9%, respectively). Several previously reported studies have shown the same response.…”
Section: Discussionmentioning
confidence: 90%
“…Our finding was the same as previously reported real‐word setting outcomes in Thailand. 16 This could potentially be explained by limited efficacy of SOF‐based regimens for GT6 infection and the small sample size. In contrast, Two studies from New Zealand ( n = 25) and United States ( n = 64) reported overall SVR rate was 96% and 95% respectively with 12 weeks of SOF/LDV.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of HCC is strongly correlated with chronic infection of hepatitis B virus, hepatitis C virus, alcoholic liver cirrhosis, etc. [ 2 , 3 ]. Conventional treatments, for patients at early stages of HCC, include surgery, radiotherapy, interventional therapy and radiofrequency ablation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%